PENGARUH PENGERINGAN KONVEKSI (CONVECTIVE DRYING) TERHADAP KECEPATAN PENGERINGAN KAYU - Sihole, Diman (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
Natural wood drying or traditional drying by using solar energy be cause it is very cheap and easy to get, is usually used in Indonesia. Because Indonesia is in the tropical region, the air condition is humid with temperatur 18 – 300C and relative humidy around 60-80% then it is not advantage to do a natural wood drying system. To reaching the wood water content 12 % is very difficult and need very long time, thus kiln dryer existence is very important to replace the natural drying system.Convective drying is usually used as a one alternative to dry the wood in the and medium furniture industries, because this drying system is relative easy to be performed and cheap. This drying system is called conventional Drying (Conventional kiln dryer).For obtaining a convective drying model it’s influence on the wood drying rate, then in this research, to be performed the measurements of the air velocity, wood width and slit distance with constant temperature, the obtaining result is by increasing the air velocity, wood width and slit distance them, the convective drying is increasing.